The Analysis of Coastal Society Vulnerabilities Against the Spread of Covid-19 in Surabaya Using the Analytical Hierarchy Process (AHP) - Ikhwani, Hasan; Satrio, Dendy; Umari, Widdi; Satrio, Sujantoko; Hadiwidodo, Yoyok Setyo; Syarifudin, Muhammad Rizky (International Journal of Marine Engineering Innovation and Research, 2025)
Coronavirus belongs to the ARI (Acute Respiratory Infection) disease, which has a high level of mortality risk. In 2019, this virus was transformed into Covid-19 with a rapid spread and a more massive impact. This disease has become a worldwide pandemic. Indonesia is a developing country and is included as one of the most densely populated countries affected by the Covid-19 pandemic, which has great potential to fail in overcoming this problem. Approximately 60% of Indonesia's population lives in coastal areas with low levels of welfare in almost all sectors of life such as social, economic, education, and health. This study aims to analyze the level of community vulnerability in the coastal area of Surabaya City by using the Analytical Hierarchy Process method. From the data taken by the survey, the results of the exposure of the Bulak Banteng Village area of Surabaya in the health, socio-cultural, economic, and general fields are 0.0469, 0.0871, 0.1809, and 0.3551, respectively. So the overall vulnerability is 0.67, which is included in the medium vulnerability criteria.